Comparison of the Efficacy between Conjugated Equine Estrogen versus Nonsteroidal Anti-inflammatory Drug for the Cessation of Uterine Bleeding among Contraceptive Implant Users: A randomized controlled trial - Polyota, Salinee; Tungmunsakulchai, Reuthairat; Tangsiriwatthana, Thumwadee (Thai Journal of Obstetrics and Gynaecology, 2024)
Objectives: To evaluate the effect of conjugated equine estrogen and nonsteroidal anti-inflammatory drugs on the controlling of abnormal uterine bleeding in hormonal subdermal implant users. Materials and Methods: Between July 2022 and April 2023, participants with etonogestrel subdermal implants who complained of abnormal uterine bleeding were randomly allocated into two groups. The study group (n = 32) received 0.625 mg of conjugated equine estrogen orally twice a daily for five days, while the control group (n = 32) received 500 mg of mefenamic acid orally three times a daily for five days. The duration of bleeding cessation was evaluated. Results: Baseline characteristics including age, BMI, duration of implant use, endometrial thickness, and pattern of bleeding were not statistically different in both groups. The duration of bleeding cessation was significantly shorter in the conjugated equine estrogen group (5.9 ± 3.4 vs 7.9 ± 3.9 days, mean difference 2.0 days (95%CI 0.01 to 0.02, p < 0.05)). Conclusion: Conjugated equine estrogen was more effective than mefenamic acid in controlling abnormal uterine bleeding in etonogestrel subdermal implant use.